Self-Cleansing Design of Rectangular Open Storm Sewer - Bong, Charles Hin Joo; Tze, Liang Lau; Aminuddin, Bin Ab Ghani (2014)
The aim of the present study is to develop incipient motion equation and design chart based on critical velocity approach for the self-cleansing design of rectangular open storm sewer. Data from experimental work on incipient motion from rectangular flumes with two different widths, namely 0.3 m and 0.6 m were subjected to multiple linear regression analysis. Selected regression models for critical velocity were further subjected to performance test by using the data from three different authors in the literature. The best regression model was proposed as the critical velocity equation and was used to develop a self-cleansing design chart. The design chart could be used to determine the minimum slope required for the purpose of self-cleansing design for the respective standard open storm sewer size available from the manufacturer of open concrete rectangular sewer.